Influence of rainfall and soil-water characteristic curve on slope stability for unsaturated soil: Case study at route 14g, Danang, Vietnam - Le Manh Thuong; Dinh Minh Tran; Tran Trung Viet (Tạp chí Khoa học và Công nghệ)
This study utilizes Geo-Slope 2D to evaluate slope stability along Route 14G, integrating soil characteristics and historical rainfall data to analyze the slope stability based on the Factor of Safety (FoS). Key findings highlight the significant role of Soil-Water Characteristic Curves (SWCCs) and permeability coefficients in determining slope responses to varying rainfall levels. Soils with higher permeability coefficients, like clayey soil 3, exhibit more rapid decreases in FoS, leading to earlier instability. The result identified a critical rainfall threshold associated with slope failure, highlighting that instability can occur before the soil is fully saturated, challenging conventional assumptions. These insights underline the importance of considering soil suction and shear strength in slope stability assessments. The findings provide essential references for developing effective landslide mitigation strategies tailored to the specific vulnerabilities of the region, thereby enhancing the safety and resilience of slopes along Route 14G.